Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/v13091718
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Increase in the Serum ANCAs in Patients with SARS-CoV-2 Infection: A Signal of Subclinical Vasculitis or an Epiphenomenon with No Clinical Manifestations? A Pilot Study

Abstract: A relationship is emerging between SARS-CoV-2 infections and ANCA-associated vasculitis (AAV) because: (i) the pulmonary involvement of COVID-19 may mimic that observed in patients with AAV; (ii) the two diseases may occur together; (iii) COVID-19 may trigger AAV. However, few cases of AAV have been identified so far in COVID-19 patients. To define the frequency of ANCA autoimmunity in patients with SARS-CoV-2 infection, we analyzed the serum ANCAs and the serum PR3 and MPO antigens by immunoassays in 124 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…The presence of ANCA was detected in patients with SARS-CoV-2 infection without overt AAV and its presence is considered an epiphenomenon due to hyperstimulation of the immune system by the infection [ 143 , 144 , 145 ]. Considering ANCA are pathogenic in AAV, whether ANCA+ COVID-19 patients may develop overt AAV during follow-up is an unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ANCA was detected in patients with SARS-CoV-2 infection without overt AAV and its presence is considered an epiphenomenon due to hyperstimulation of the immune system by the infection [ 143 , 144 , 145 ]. Considering ANCA are pathogenic in AAV, whether ANCA+ COVID-19 patients may develop overt AAV during follow-up is an unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection induces an exaggerated immune response in susceptible individuals [ 1 , 2 ]. The development of autoantibodies in a tiny minority is consequential to the release of Proteinase-3 (PR-3), Myeloperoxidase (MPO) and other antigens by the neutrophils in response to SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Although further studies should be continued, it was identified that myeloperoxidase (MPO) titer has been increased after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in a pilot study. 3 Despite that the immune responses after natural infection with SARS-CoV-2 and mRNA vaccination could differ, there have been concerns about antineutrophil cytoplasmic antibody (ANCA) vasculitis after COVID-19 vaccines. 4 …”
Section: Introductionmentioning
confidence: 99%